Unexpectedly Streamlined Mitochondrial Genome of the Euglenozoan Euglena gracilis - Dobáková, Eva; Flegontov, Pavel; Skalický, Tomáš; Lukeš, Julius (Oxford University Press, 2015)
In this study, we describe the mitochondrial genome of the excavate flagellate Euglena gracilis. Its gene complement is reduced as compared with the well-studied sister groups Diplonemea and Kinetoplastea.We have identified seven protein-coding genes: Three subunits of respiratory complex I (nad1, nad4, and nad5), one subunit of complex III (cob), and three subunits of complex IV (cox1, cox2, and a highly divergent cox3).Moreover, fragments of ribosomalRNAgenes have also been identified.Genes encoding subunits of complex V, ribosomal proteins and tRNAs were missing, and are likely located in the nuclear genome. Although mitochondrial genomes of diplonemids and kinetoplastids possess themost complex RNA processingmachineries known, including trans-splicing and editing of the uridine insertion/deletion type, respectively, our transcriptomic data suggest their total absence in E. gracilis. This finding supports a scenario inwhich the complexmitochondrial processingmachineries of both sister groups evolved relatively late in evolution from a streamlined genome and transcriptome of their common predecessor.
Keywords: Euglena gracilis; mitochondrial genome; transcription; RNA editing